The Child Protection Policy of the Reformed Church in Hungary - Homicskó, Olivér Árpád; Birinyi, Márk (Religion and Children's Rights, 2025)
Abstract:This study summarises the activities of the Reformed Church in Hungary in the field of child protection, with particular reference to institutionalised child protection services. The Church’s child protection policy is biblically based, allowing for personal interpretation and application of the biblical teachings. The church operates a child protection network, including family transition homes, Sure Start Children’s Homes and after-school study halls. The network also includes the Hungarian Reformed Child Protection Service – Foster Parent Network, which provides foster care for children in need. The ultimate aim is to either reunite children with their birth families or to find adoptive families.Keywords: child protection, child protection activities of the Reformed Church in Hungary, best practice, biblical foundation, specificities of assistance